Feasibility and acceptability of expressive writing with postpartum women: a randomised controlled trial - Crawley, Rosalind (2018)
Background: Pregnancy, birth and adjusting to a new baby is a potentially stressful time that can negatively affect women’s mental and physical health. Expressive writing, where people write about a stressful event for at least 15 min on three consecutive days, has been associated with improved health in some groups but it is not clear whether it is feasible and acceptable for use with postpartum women. This study therefore examined the feasibility and acceptability of expressive writing for postpartum women as part of a randomised controlled trial (RCT). Methods: The Health After Birth Trial (HABiT) was an RCT evaluating expressive writing for postpartum women which included measures of feasibility and acceptability. At 6 to 12 weeks after birth 854 women were randomised to expressive writing, a control writing task or normal care, and outcome measures of health were measured at baseline, one month later and six months later. Feasibility was measured by recruitment, attrition, and adherence to the intervention. Quantitative and qualitative measures of acceptability of the materials and the task were completed six months after the intervention. Results: Recruitment was low (10.7% of those invited to participate) and the recruited sample was from a restricted sociodemographic range. Attrition was high, increased as the study progressed (35.8% at baseline, 57.5% at one month, and 68.1% at six months) and was higher in the writing groups than in the normal care group. Women complied with instructions to write expressively or not, but adherence to the instruction to write for 15 min per day for three days was low (Expressive writing: 29.3%; Control writing: 23.5%). Acceptability measures showed that women who wrote expressively rated the materials/task both more positively and more negatively than those in the control writing group, and qualitative comments revealed that women enjoyed the writing and/or found it helpful even when it was upsetting. Conclusions: The feasibility of offering expressive writing as a universal self-help intervention to all postpartum women 6 to 12 weeks after birth in the HABiT trial was low, but the expressive writing intervention was acceptable to the majority of women who completed it.